One-Dimensional and Two-Dimensional Zn(II) Coordination Polymers with Ditopic Imidazo[1,5-a]pyridine: A Structural and Computational Study - Sozzi, Mattia; Chierotti, Michele R.; Gobetto, Roberto; Gomila, Rosa M.; Marzaroli, Vittoria; Priola, Emanuele; Volpi, Giorgio; Zago, Stefano; Frontera, Antonio; Garino, Claudio (Molecules (Basel, Switzerland), 2024)
Zn(II) coordination polymers are being increasingly studied for their stability and properties. Similarly, there is a growing interest in imidazo[1,5-a]pyridine derivatives, which show great potential in luminescence and pharmaceutical applications. In this work, we successfully synthesized and crystallized three new coordination polymers, using Zn(II) as the metallic node, dicarboxylic acids of different length and nature as linkers, and a linear ditopic imidazo[1,5-a]pyridine derivative, to explore the role of this molecule as a propagator of the dimensionality of the structure or as an ancillary ligand. Our work demonstrates the structural capability of imidazo[1,5-a]pyridines in an unexplored domain for this family of ligands. Notably, we observed a pronounced ability of this heterocyclic scaffold to establish π···π interactions in the solid state. The supramolecular π-stacked assemblies were theoretically analyzed using DFT calculations based on model structures.